Investigating Students’ Reading Strategies and Reading Comprehension Through Digital Literacy Environment - M, Asia; Asdam, Muhammad; Asdar, Asdar (STAI Hubbulwathan Duri, 2024)
Educational technology provides students the chance to learn online and develop independent learners. The availability of digital learning materials is an attempt to realize exactly a widespread learning strategy. This study aimed to investigate the effect of the impact of providing detailed instructions on reading strategies and reading comprehension through a digital literacy environment (DLE) for university students. The research employed a qualitative approach through survey data, and it was conducted in an undergraduate education department at the State University of Makassar, which had 43 students. The findings indicate that students generally acknowledge the effectiveness of digital technologies, such as a private Facebook group and WhatsApp, in providing inclusive and secure platforms for student involvement. These platforms create a comfortable environment for students to share their thoughts. The students were motivated when using digital tools like e-books, interactive reading platforms, and multimedia resources. It can be concluded that discussion groups on Facebook and WhatsApp offer comprehensive, confidential forums for students to improve their digital reading comprehension.